The Course of Research into the Economic Consequences of German Works Councils - John T. Addison; Claus Schnabel; Joachim Wagner (Institute for the Study of Labor (IZA), 2003)
In a survey published in the British Journal of Industrial Relations, Frege (2002) evaluates research on the German works council from the perspective of several disciplines, including economics. Ultimately, she concludes that economic analysis of the works council has reached a ?dead end?. The present treatment offers a very different conclusion based on a more encompassing review of the evidence. It will identify three distinct phases in the economic analysis of codetermination at the workplace. This framework is key to understanding the progress that has been made in analysing the effect of works councils on firm performance, while highlighting some important measurement issues and diversity of finding. Given the recent vintage of much of the German research, it is inevitable that Frege considers studies from just the first two phases. Rather interestingly, it is the neglected third phase of research that contains some of the most favourable evaluations to date of works council impact.
Keywords: J50; 330; works councils; codetermination; quits; productivity; investment; profitability; employee involvement/high performance workplace practices; Mitbestimmung; Betriebsrat; Wirtschaftsforschung; Deutschland